The effect of high-intensity interval swimming training on CREB and ERK proteins of hippocampus tissue in elderly rats - Zahra Sabri; Mozhgan Ahmadi (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: Cognitive impairment caused by aging has become one of the most common health threats in many countries. Signaling pathways are important moderators of various physiological and pathological processes, and abnormal activation of some signaling pathways can play a role in disease progression in old age. Targets of intracellular signaling in response to exercise have been intensively studied as a measure of cellular processes that occur following specific conditions. It has been found that exercise increases neurogenesis through the induction of neural factors in the hippocampus, which is associated with improved cognitive performance, since long-term exercise can improve the age-related impairment in hippocampal neurogenesis. The aim of this study was to evaluate the effect of high-intensity interval swimming training on CREB and ERK proteins of hippocampus tissue in elderly rats.Materials and Methods: In this experimental study, 12 aged male Sprague-Dawley rats (20 months old and average weight 300-450 gr) were placed in two control groups (n= 6 rats) and high-intensity interval swimming training (n= 6 rats). Rats in the training group performed high-intensity interval training (HIIT), including 14 times of 20 seconds of swimming with 10 seconds of rest between each time. The exercise program was carried out for six weeks (three days a week, one day in between). 48 hours after the last training session, rats were anesthetized and immediately, using a surgical blade, the skull was split and the brain was carefully removed. The healthy brain was divided into two halves by a surgical blade, and according to the coordinates of the hippocampus, the hippocampal sinus was separated from the limbic system with the help of a clean atlas. The content of cAMP-response element binding protein (CREB) and Extracellular signal-regulated protein kinases 1 and 2 (ERK) proteins in hippocampal tissue was measured by Western blotting. Data were analyzed using independent t-test at the P <0.05.Results: The results showed that the protein content of ERK and CREB in the hippocampus of elderly rats after six weeks of training was significantly higher (P=0.03 and P=0.001, respectively) than untrained rats.Conclusion: According to the results of high-intensity interval swimming training leads to a significant increase in the content of cAMP-response element binding protein and Extracellular signal-regulated protein kinases 1 and 2 of the hippocampus tissue in aged rats, so probably high-intensity interval swimming training can help improve factors involved in cognitive ability during aging.